PENGARUH BANK SPESIFIK TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Asfarini, Khairunnisa; Nasution, Dewi Sartika; Syapriatama, Imronjana (Universitas Islam Negeri Mataram, 2022)
This study aims to determine the effect of Bank Spesifics that contain BOPO, FDR and CAR onBank Profitability which proxied by ROA, of Islamic Commercial Banks for the period 2018-2021. This study uses OLS estimation methods with the population in the study 15 IslamicCommercial Banks in Indonesia. The number of samples consists of the financial statements ofIslamic banks during 2018-2021. The sampling technique employes purposive sampling method.The results of this study indicate that the BOPO and FDR have no effect on ROA meanwhileCAR has positive and significant effect on ROA.